Neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios as predictive and prognostic markers in patients with locally advanced rectal cancer treated with neoadjuvant chemoradiation - Dudani, Shaan; Marginean, Horia; Tang, Patricia A; Monzon, Jose G; Raissouni, Soundouss; Asmis, Timothy R; Goodwin, Rachel A; Gotfrit, Joanna; Cheung, Winson Y; Vickers, Michael M (Université d'Ottawa | University of Ottawa, 2019)
Abstract Background A standard therapy for locally advanced rectal cancer (LARC) includes fluoropyrimidine (FP)-based neoadjuvant chemoradiation (nCRT). Previous studies have inconsistently demonstrated that baseline neutrophil- and platelet-to-lymphocyte ratios (NLR and PLR) are predictive of response to nCRT or prognostic of outcomes in LARC. Methods We reviewed patients with LARC undergoing nCRT followed by surgery from 2005 to 2013 across 8 Canadian cancer centres. Outcome measures of interest were pathological complete response (pCR), disease-free survival (DFS) and overall survival (OS). Logistic regression and Cox proportional hazard models were used to assess for associations between baseline hematologic variables and outcomes. Results Of 1527 identified patients, 1237 (81%) were included in the DFS/OS analysis. Median age was 62 (range 23–88), 69% were male, and 80% had performance status (PS) 0–1. Twenty-six percent had elevated NLR (≥ 4), and 66% had elevated PLR (≥ 150). Ninety-seven percent of patients received FP-based nCRT, with 96% receiving ≥44 Gy. 81% completed neoadjuvant chemotherapy and 95% completed neoadjuvant radiotherapy, with a pCR rate of 18%. After a median follow-up time of 71 months, 8% developed local recurrence, 22% developed distant recurrence and 24% died. 5-year DFS and OS were 69% (95% CI 66–72%) and 79% (95% CI 77–82%), respectively. In multivariate analyses, elevated baseline NLR and PLR were neither prognostic for DFS and OS nor predictive of pCR. Conclusions NLR and PLR were not found to be independently prognostic for DFS or OS and did not predict for pCR in patients with LARC undergoing nCRT followed by surgery.